Can spontaneous spinal epidural haematoma be managed safely without operation? a report of four cases. Issue 6 (1st December 2000) - Duffill, J; Sparrow, O C; Millar, J; Barker, C S
Abstract : The presentation, investigation, and management of four patients with spontaneous spinal epidural haematoma is presented. In each case the diagnosis was made by MRI. At the time of diagnosis spontaneous recovery had started in each patient and therefore they were all treated conservatively. In each case follow up MRI confirmed rapid reduction in the size of the haematoma and no underlying cause was demonstrated. The presentation, diagnosis, and rationale for treatment are discussed. Conservative treatment is safe in some cases of spinal epidural haematoma if early neurological recovery has started.